Spaces for interactive engagement or technology for differential academic participation? Google Groups for collaborative learning at a South African University - Rambe, Patient (Journal of Computing in Higher Education, 2017)
The rhetoric on the potential of Web 2.0 technologies to democratize online engagement of students often overlooks the discomforting, differential participation and asymmetrical engagement that accompanies student adoption of emerging technologies. This paper, therefore, constitutes a critical reality check for student adoption of technology to the extent that it explores the potential of Google Groups (i.e. self-organised online groups) to leverage collaborative engagement and balanced participation of students with minimal educator support. Community of Inquiry and a case study approach involving in-depth interviews with racially mixed students and Google Group artifacts were drawn upon as theoretical and methodological lenses for examining the equality of participation, academic rigor and complexity of engagement in Google Groups. Study findings were mixed: a semblance of authentic peer-based engagements, emergent academic networking, and inter-racial communication in Google Groups was juxtaposed with gender asymmetries in participation, dominance of group administrators’ postings and shallow collaborative engagements. The study, therefore, recommends actively engaged Group leaders who steer gender and racially balanced engagements, scaffold peer on-task behavior; including a sound pedagogical strategy anchored in collaborative problem-solving; authentic construction of knowledge; effective completion of collaborative tasks by students; and constructive assessments by the educator and peers.
Published Article
Keywords: Google Groups; Collaborative engagement; Academic participation; Collaborative learning